High rate treatment system in stormwater harvesting and reuse in urban areas / S. Vigneswaran and J. Kandasamy - Vigneswaran, S.; Kandasamy, J. (2012)
Expanding the beneficial reuse of stormwater runoff lowers the demand placed on municipal water supplies and reduces water pollution. This study analysed the water quality of stormwater collected at Carlton, in Kogarah, Sydney. Water quality measurements in terms of physical, chemical, biological and organic characteristics were taken and compared against Australian average values and against drinking water standards. Suitable technology to treat this stormwater for potable and non-potable reuse was evaluated. Stormwater for harvesting and reuse purposes should be assessed primarily for nutrients, physical properties (suspended solids, turbidity), bacteriological properties (total and faecal coliform), heavy metals (such as iron, manganese and lead), and organic matter since it is more unlikely to meet these water parameters. Stormwater discharge is relatively high and therefore needs to be treated at a high rate. High rate treatment systems have relatively high removal rates of nutrients (total nitrogen and total phosphorus), suspended solids or turbidity, heavy metals such as iron, manganese and lead, and dissolved organic matter. These systems are compact and do not require a significant land footprint as there is no need to store water before pretreatment. This makes these systems suitable for treatment for stormwater harvesting and reuse. The alternative is to store the stormwater before treatment in a manner similar to current stormwater management treatment systems. These systems are viable where there is less space constraints.